2003
DOI: 10.1088/0034-4885/66/5/203
|View full text |Cite
|
Sign up to set email alerts
|

Optical interferometry in astronomy

Abstract: Abstract. Here I review the current state of the field of optical stellar interferometry, concentrating on ground-based work although a brief report of space interferometry missions is included. We pause both to reflect on decades of immense progress in the field as well as to prepare for a new generation of large interferometers just now being commissioned (most notably, the CHARA, Keck and VLT Interferometers). First, this review summarizes the basic principles behind stellar interferometry needed by the lay… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
250
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(256 citation statements)
references
References 240 publications
(382 reference statements)
3
250
0
3
Order By: Relevance
“…The resulting computational load is substantially lighter and allows for faster and more complete Monte Carlo searches. A detailed review of optical interferometry in astronomy can be found in Monnier (2003). A detailed discussion of phases in particular is continued in Monnier (2007), including expansive discussions on closure phase, and more esoteric observables possible with optical interferometers, such as differential closure phase, closure differential phase, and closure amplitudes.…”
Section: Observational Quantities Predictionsmentioning
confidence: 99%
“…The resulting computational load is substantially lighter and allows for faster and more complete Monte Carlo searches. A detailed review of optical interferometry in astronomy can be found in Monnier (2003). A detailed discussion of phases in particular is continued in Monnier (2007), including expansive discussions on closure phase, and more esoteric observables possible with optical interferometers, such as differential closure phase, closure differential phase, and closure amplitudes.…”
Section: Observational Quantities Predictionsmentioning
confidence: 99%
“…However, the absolute value of the phase is lost because of random atmospheric perturbations. By adding the phases of the fringes measured for each baseline over a 3-telescope configuration, one can measure the closure phase, which is insensitive to atmospheric disturbances (Jennison 1958;Monnier 2003). The closure phase includes part of the Fourier phase information, and is related to the global asymmetry of the emission: a point-symmetric object has a zero closure phase.…”
Section: Image Reconstruction Processmentioning
confidence: 99%
“…On the other hand, at L , the source looks quite symmetrical. We note that maximumentropy (MEM) images usually have a super-resolution beyond the diffraction limit, since the reconstruction depends only on the entropy statistics (for a more detailed description, see Monnier 2003;Monnier & Allen 2013). Images presented in Fig.…”
Section: The Core Of Irs 9a Probed By K and L-band Sam Datamentioning
confidence: 99%